2011
DOI: 10.1128/jcm.02474-10
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of In Vitro Susceptibility Characteristics of Candida Species from Cases of Invasive Candidiasis in Solid Organ and Stem Cell Transplant Recipients: Transplant-Associated Infections Surveillance Network (TRANSNET), 2001 to 2006

Abstract: Invasive fungal infections (IFI) are a major cause of morbidity and mortality among both solid organ transplant (SOT) and hematopoietic stem cell transplant (HSCT) recipients. Candida is the most common cause of IFI in SOT recipients and the second most common cause of IFI in HSCT recipients. We determined susceptibilities to fluconazole, voriconazole, itraconazole, posaconazole, amphotericin B, and caspofungin for 383 invasive Candida sp. isolates from SOT and HSCT recipients enrolled in the Transplant-Associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 31 publications
2
32
1
1
Order By: Relevance
“…On the contrary, as reported in other recent surveys (Pfaller et al, 2011b;Arendrup et al, 2011a;Lockhart et al, 2011), we demonstrated that cases of decreased susceptibility to fluconazole were frequent and increasing. Overall, the median rate of cases of fluconazole resistance in the 11 centres reporting at least ten episodes of deep-seated Candida infection was 17.8 %, with proportions of cases ranging from 4.3 to 28.6 %.…”
supporting
confidence: 67%
“…On the contrary, as reported in other recent surveys (Pfaller et al, 2011b;Arendrup et al, 2011a;Lockhart et al, 2011), we demonstrated that cases of decreased susceptibility to fluconazole were frequent and increasing. Overall, the median rate of cases of fluconazole resistance in the 11 centres reporting at least ten episodes of deep-seated Candida infection was 17.8 %, with proportions of cases ranging from 4.3 to 28.6 %.…”
supporting
confidence: 67%
“…Previous efforts to reduce the incidence of fungemia have relied mostly on systemic antifungal prophylaxis, which can increase the incidence of antifungal resistance among fungal isolates. 22 If our results are confirmed, topical use of chlorhexidine could be added to strategies to prevent fungal infections.…”
Section: Discussionmentioning
confidence: 70%
“…The reason for this increase is unknown, but there is speculation that it is due to the widespread use of azoles (to which C. glabrata has decreased susceptibility) for treatment and prophylaxis of fungal infections. As an example, C. glabrata is the most prevalent Candida species among hematopoietic stem cell transplant recipients, a cohort of patients with a very high rate of antifungal prophylaxis (16,30). There is speculation that because of its haploid genome, C. glabrata may be able to develop tolerance or resistance to azoles more easily than other species of Candida.…”
Section: The Curious Case Of Candida Glabratamentioning
confidence: 99%